2022
DOI: 10.1111/ijlh.13794
|View full text |Cite
|
Sign up to set email alerts
|

Stability of coagulation parameters in plasma samples at room temperature after one freeze/thaw cycle

Abstract: In clinical laboratories, the pre-analytical step is crucial for coagulation assays because it can influence the results and consequently clinical decision-making. Pre-analytical variables, such as blood sampling, transportation, processing and storage (with time and temperature as variables), influence the haemostasis results. 1 Many data are available on the stability of coagulation parameters and storage conditions (e.g. room temperature (RT) versus 4°C, stability over time) for fresh plasma and whole blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The aim was to reduce the risk of bias due to the stability of edoxaban in plasma after thawing. Recent data showed that the coagulation parameters' stability in samples containing apixaban or rivaroxaban, at room temperature after one freeze/thaw cycle, was 3 and 2 h, respectively 33 . To our knowledge, no data are available for edoxaban in the same context, but we took this precaution as a conservative approach.…”
Section: Methodsmentioning
confidence: 99%
“…The aim was to reduce the risk of bias due to the stability of edoxaban in plasma after thawing. Recent data showed that the coagulation parameters' stability in samples containing apixaban or rivaroxaban, at room temperature after one freeze/thaw cycle, was 3 and 2 h, respectively 33 . To our knowledge, no data are available for edoxaban in the same context, but we took this precaution as a conservative approach.…”
Section: Methodsmentioning
confidence: 99%
“…However, owing to the centralization of laboratories and the need for specialized analyses, controls, or clinical studies, plasma samples may be frozen and stored for later analysis. The stability of frozen samples has been extensively studied and may vary with the storage temperature (−20 • C or −80 • C) or the thawing mode [4,5].…”
mentioning
confidence: 99%